A monitoring and data analysis method for microplastics in marine sediments. (January 2023) - Bäuerlein, Patrick S.; Erich, Maarten W.; van Loon, Willem M.G.M.; Mintenig, Svenja M.; Koelmans, Albert A.
Abstract: In Europe, policy frameworks demand the monitoring of microplastics in marine sediments. Here we provide a monitoring and data analysis method for microplastic particles designed to be used in the context of Marine Strategy Framework Directive (MSFD) and OSPAR policy frameworks. Microplastics were analysed in marine sediments at four different locations in Dutch coastal and transitional waters using replicate sampling to investigate micro-spatial variation. Particle size distribution followed a power law with slope 3.76. Thirteen polymers were identified, with their composition varying between sediments near densely populated West coast areas versus the more rural Wadden Sea area. We quantify differences in the micro-spatial variation of microplastic concentrations between locations using the relative standard error of the mean (RSEM). This metric provides an opportunity to optimize the sensitivity of trend detection in microplastic monitoring networks by selecting locations with relatively low micro-spatial variation. We provide a method to optimize the number of replicate samples for a given location using its relationship with the RSEM. Two replicate samples appear to be cost-effective for relatively homogenous locations, whereas more heterogenous locations require four replicates. Highlights: Improved monitoring and data analysis with potential relevance for MSFD and OSPAR monitoring of microplastics in sediments. A data analysis method is provided that allows for the optimization of the number of replicates used for specific locations RSEM model can be used for a cost-effective choice of the number of subsamples to be analysed. For relatively homogenic locations two samples can be cost-effective, more heterogenic locations can require four samples